Hurricanes Induced Irreversible Large‐Scale Loss of Mangrove Forests - Xixing Liang; Zhijun Dai; Xuefei Mei; Riming Wang; Wenjun Zeng; Sergio Fagherazzi (Geophysical Research Letters)
Abstract Mangrove forests act as effective natural barriers against tropical storms. However, little information is available on the resilience of mangrove forests against hurricane impacts. Here we quantify the response of Florida mangroves to hurricane forcing. We found that the mangrove area in South Florida experienced four sharp declines over the past thirty years, with a slow recovery trend observed after each decline. The loss of mangroves displayed an exponential decrease from the ocean to the upland during tropical cyclones, while the vegetation fringe underwent seaward extensions in fair‐weather periods. Hurricanes of category three or higher were responsible for the sharp declines in mangroves, while sea‐level rise was not related to vegetation loss. We project that mangroves loss in Florida mangrove can total 533 km2 by 2050 and 1,956 km2 by 2100, driven by an increase in frequency and intensity of tropical cyclones.